Ammonia inhibition and toxicity in anaerobic digestion: A critical review. (December 2019) - Jiang, Ying; McAdam, Ewan; Zhang, Yue; Heaven, Sonia; Banks, Charles; Longhurst, Philp
Abstract: As a waste management technology which offers environmental benefit and renewable energy production, anaerobic digestion (AD) has become the preferred technology for the treatment of organic waste. However, in such waste streams nitrogen contents are likely to be high. There is prevailing literature evidence suggests that high ammonia concentration especially its free molecular form (NH3 ), derived from nitrogen content in substrates is the cause of inhibition and sudden failure of the AD process. This paper comprehensively reviews previous knowledge from digestion studies using high nitrogen waste streams as feedstocks and critically analysed the considerable variations in the inhibition/toxicity levels reported for ammonia. Literature evidences suggest methanogens, particularly acetoclastic methanogens are most susceptible to ammonia toxicity, and therefore this review has a particular focus on the mechanism of the 'selective' inhibition to methanogens and the impact of ammonia toxicity to the overall methanogen population in an AD digester. This population change explains in many reported cases that sufficient acclimatisation can significantly alleviate the phenomenon of inhibition and specific requirement of certain trace nutrients. Currently available mitigation strategies for high nitrogen content feedstock digestion are reviewed and discussed in relation to the population change and trace nutrient requirements.